Regulation of Inflammatory Response by Transmembrane Adaptor Protein LST1 - Fabisik, Matej; Tureckova, Jolana; Pavliuchenko, Nataliia; Kralova, Jarmila; Balounova, Jana; Vicikova, Kristina; Skopcova, Tereza; Spoutil, Frantisek; Pokorna, Jana; Angelisova, Pavla; Malissen, Bernard; Prochazka, Jan; et al. (Frontiers in Immunology, 2021)
LST1 is a small adaptor protein expressed in leukocytes of myeloid lineage. Due to the binding to protein tyrosine phosphatases SHP1 and SHP2 it was thought to have negative regulatory function in leukocyte signaling. It was also shown to be involved in cytoskeleton regulation and generation of tunneling nanotubes. LST1 gene is located in MHCIII locus close to many immunologically relevant genes. In addition, its expression increases under inflammatory conditions such as viral infection, rheumatoid arthritis and inflammatory bowel disease and its deficiency was shown to result in slightly increased sensitivity to influenza infection in mice. However, little else is known about its role in the immune system homeostasis and immune response. Here we show that similar to humans, LST1 is expressed in mice in the cells of the myeloid lineage. In vivo, its deficiency results in alterations in multiple leukocyte subset abundance in steady state and under inflammatory conditions. Moreover, LST1-deficient mice show significant level of resistance to dextran sodium sulphate (DSS) induced acute colitis, a model of inflammatory bowel disease. These data demonstrate that LST1 regulates leukocyte abundance in lymphoid organs and inflammatory response in the gut.